Sex-specific strategies of dentine depletion in red deer - Carranza, Juan; Mateos, Concha; Alarcos, Susana; Sánchez-Prieto, Cristina B.; Valencia-Ruíz, Juliána (Oxford Academic, 2008)
Worn teeth in herbivore ungulates may be related to lower efficiency in mastication and hence lower performance. However, selection should favour maximal performance in terms of body mass and reproductive capacity during reproductive lifespan, when permanent teeth are already partially worn. We hypothesize that wear rate may respond to a strategy of use of tooth materials (notably dentine), which balances instantaneous wear rate and performance against tooth preservation for future performance and reproduction. In the present study, we investigated 4151 carcasses of Iberian red deer Cervus elaphus hispanicus and show that more worn molars were not related to lower performance throughout age. By comparing between sexes, tooth wear rates were smaller in females than in males, but the relationship between tooth wear and body performance also differed between the sexes: females did not show a significant relationship between tooth wear and performance but males with more worn teeth were in general heavier and had larger antlers until senile age, when more depleted teeth were related to smaller antlers. These results reveal, for the first time, sex-specific lifetime strategies of dentine expenditure: maintenance of performance ability throughout a longer reproductive lifespan in females, compared with maximizing current performance by depleting dentine reserves within a shorter lifespan in males.
Keywords: Ciervos - Reproducción; Cervus elaphus; life history; senescence; sexual selection; teeth